Two new species and a new record of Spininola from China (Lepidoptera: Nolidae: Nolinae) - Hu, Yan-Qing; Wang, Min; Han, Hui-Lin (Zootaxa, 2012)
The small genus Spininola was recently erected by László, Ronkay & Witt (2010) with the type species Nola loxoscia Hampson, 1900. They tabulated six species in the genus, S. loxoscia (Hampson, 1900), S. vesiculalis (Eecke, 1926), S. trilinea (Marumo, 1923), S. denticulata (Moore, 1888), S. fuscibasalis (Hampson, 1896) and S. armata László, Ronkay & Witt, 2010 from Thailand. The genus is distributed in eastern Asia, from Nepal and Sri Lanka in the west, to Japan in the north and Sumatra in the south. In our surveys, two new species were found and are described herein, and S. loxoscia (Hampson, 1900) is recorded for the first time from China (Fig. 1).